A Critical Review on the Book A Secular Age - Mahdi Abootalebi Yazdi; Ali Moradkhani; Meysam Sefid Khosh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The basis of the theory of secularism is that as modernity progresses (a set of phenomena including science, technology, and rational forms of authority), the influence of religion gradually diminishes, but Charles Taylor argues that the modern world not only hasn’t destroyed religion, but also in many cases, has led to its growth and development. The book The Secular Age is a detail of his views on secularism. Taylor talks about situations in the past where belief in God was pervasive, but things developed in such a way that belief in God became an option among other options. He describes the process of spreading secularism in the new West and what has happened to religion. In this process, for the religious, "God" and for the non-religious, "reason" describes perfection. This article, with a brief look at Taylor's work, examines the movement of the West (Western Europe and North America) from religious societies to secular societies, and after analyzing Taylor's theory of secularism, critiques and summarizes his ideas.